Effects of Parboiling and Physico-Chemical Characteristics of Rice on the Glycemic and Insulinemic Indices in Type 2 Diabetic Subjects (Ibrahim Medical College Journal, 2009)
Background and Purposes: To observe the influence of parboiling, amylose content and gelatinization temperature of rice on plasma glucose and insulin responses in type 2 diabetic subjects because diabetic subjects are especially prescribed usage of starchy foods with low glycemic responses. Methods: Seventeen type 2 diabetic subjects ingested five test meals of 50g available carbohydrate as white bread, cooked rice with high (29%) and low amylose content (13%), undergoing different processing and gelatinization temperatures. The diets were taken in a random order after a 10h overnight fast with approximately 7 days interval as wash out period. Results: The glycemic index (GI) of all rice varieties were lower than that of white bread (p